Penggunaan Teknik Kolase terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun PAUD Warci Jaya Tahun Ajaran 2017-2018 - Neng Riska Puspitasari; Indra Zultiar (utile: Jurnal Kependidikan, 2018)
The study entitled "the use of fine motor ability of children ages 5-6 years old PAUD Warci Jaya school year 2017-2018". To develop fine motor ability in children needed a technique or an appropriate learning activities so that fine motor ability assets could be developed. These researchers use quantitative research design with a kind of quasi experiment method (Quasi Exsperiment design) with the subject research group B amounted to 24 children. Research data collected is analyzed using statistics analysis and testing techniques using a t-score. As for the testing of hypotheses, observations indicate that in the use of collage technique against fine motor ability of children aged 5-6 years in old PAUD Warci jaya increased with results thitung = 22.05 of ttabel = 1.71088. The results of this study stated that through the activity of the collages can be enhance fine motor ability in children ages 5-6 years. Thus it can be concluded that by applying the technique of collage activities can improve fine motor ability of children Group B in PAUD Warci Jaya.